ANALISIS EFEKTIVITAS KINERJA PADA PT AGRO MUKO DENGAN PENDEKATAN BALANCED SCORECARD KABUPATEN MUKOMUKO - Ahmad Sumarlan; Melisa Ade Kartika (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to measure the effectiveness of the performance of PT. Agro Muko, Mukomuko Regency, using the Balanced Scorecard approach, which includes four perspectives: financial, customer, internal business processes, and growth and learning. The research method used is a qualitative descriptive method with a case study approach, where data was collected through observation, interviews, and documentation during the period of January to February 2024. The results of the study indicate that from a financial perspective, the company was able to achieve cost effectiveness with an excellent ROA value for three consecutive years. The customer perspective shows high satisfaction with the company's service and product quality. From the perspective of internal business processes, the company innovates products and services that support sustainability and market expansion. Meanwhile, from the perspective of growth and learning, employee productivity still needs to be improved even though the employee retention rate is quite good. The conclusion of this study shows that the use of the Balanced Scorecard provides a comprehensive overview of company performance and can be a strategic tool in performance planning and evaluation. Keywords: Performance Effectiveness, Balanced Scorecard